Students and Teachers' Perception of the Use of Explicit Grammar Instruction in Ten Graders' Writing Class in Senior High School in Indonesia - Izza, Novrita Nurul; Kuswardani, Rahayu (RETAIN : Journal of Research in English Language Teaching, 2023)
Explicit grammar teaching is a popular type of teaching in many countries and is known to show positive results and have a positive effect on students' academic achievement. This is because teaching grammar is important, especially for English teachers, because there is a combination of writing assessment, grammar knowledge, and accuracy to complete the entire assessment score. The purpose of this research is to fill a need by studying the use of explicit grammar instruction in EFL classes in Indonesia. The study used a qualitative research technique and four data collection instruments: interviews, field notes, observation sheets, and questionnaires. The data collection was conducted in the classroom of tenth students at Senior High School. The results showed that the instructor believes that specific grammar instruction is vital. From the results regarding students' perception, it was found that 35 participants showed positive perceptions regarding the application of grammar instructions used in narrative texts. They also claim that using grammar instructions to study narrative texts can help them understand the material more easily. Further, from the teachers' perception, it can be known that the teacher feels that explicit grammar instruction is very important, especially in teaching narrative texts, because there are many uses of grammar that must be considered in such texts. It helps students understand the text and understand the language features in the narrative text.